PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN IT BALANCE SCORECARD DI KAMPUS AMIK AKMI BATURAJA - Dian Sri Agustina; Yunita Trimarsiah (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2017)
Nowadays, the Strategic planning information system was one of the keys in achieving an organization, one of them was at campus of AMIK AKMI Baturaja, where the development of information technology could help to improve the quality and service to the students so that they could produce the quality that was ready to compete. Therefore, this research had the aim to create the strategic planning of information system to increase the performance of Job. The Strategic Planning Model of Information system that would be discussed in this case was by using IT Method of Balance Scorecard. The result of research showed a strategic planning model of information system, which mapped into four BSC IT perspective, they were the orientation of the user's perspective, the contribution of the company, the operational improvement, and the future orientation. To clarify the results of the analysis used tools: SWOT and MC Farlan's. The results of strategic planning were in the form of framework and the future application portfolio. To measure and examine the strategic planning was created, used a SI performance measure, namely IT Balanced Scorecard (BSC). Strategic planning was expected to be the best answer to the problems faced.